2019
DOI: 10.1111/ggi.13770
|View full text |Cite
|
Sign up to set email alerts
|

Which factors are associated with length of stay in older patients with acute decompensated heart failure with preserved ejection fraction?: AURORA study

Abstract: Aim In heart failure with preserved ejection fraction (HFpEF), it is unclear which factors on admission are correlated with long stays. In contrast, acute decompensated heart failure (ADHF) in older patients is associated with a high risk of a long stay. To manage older ADHF patients with HFpEF, it is important to reveal the risk factors for a long stay on admission. Methods We enrolled consecutive older patients (aged >75 years) with HFpEF (ejection fraction ≥50%) who were admitted to control ADHF from May 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…For this reason, several nutritional assessment tools in hospitalized patients with heart failure had incorporated serum albumin in their patient evaluation [ 58 , 59 ]. In terms of LOS, one study in Japan reported that hypoalbuminemia was associated with prolonged LOS [ 21 ], which was in accordance with our results. However, only patients with HFpEF were included in that study, whereas our study included a broader spectrum of patients with heart failure.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For this reason, several nutritional assessment tools in hospitalized patients with heart failure had incorporated serum albumin in their patient evaluation [ 58 , 59 ]. In terms of LOS, one study in Japan reported that hypoalbuminemia was associated with prolonged LOS [ 21 ], which was in accordance with our results. However, only patients with HFpEF were included in that study, whereas our study included a broader spectrum of patients with heart failure.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, several studies had identified other predictors of prolonged LOS in patients with heart failure such as gender [ 8 , 21 ], a number of comorbidities [ 9 ], severity of disease [ 9 ], and low systolic blood pressure (< 155 mmHg) on admission [ 21 ]. Almost all potential predictors included in our study showed statistical significance in univariable analysis, except for the male gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have read with great interest the article by Nishino et al 1 The authors aimed to reveal the risk factors associated with long hospital stays in patients with heart failure (HF) with preserved ejection fraction who were admitted to hospital with acute decompensated HF. They compared the baseline characteristics of the short-and long-stay groups.…”
Section: Commentsmentioning
confidence: 99%
“…
COMMENTSSome comments for better understanding of the study entitled "Which factors are associated with length of stay in older patients with acute decompensated heart failure with preserved ejection function? : AURORA study"Dear Editor,We have read with great interest the article by Nishino et al 1 The authors aimed to reveal the risk factors associated with long hospital stays in patients with heart failure (HF) with preserved ejection fraction who were admitted to hospital with acute decompensated HF. They compared the baseline characteristics of the short-and long-stay groups.
…”
mentioning
confidence: 99%